Influence of the fuel quantity on the spray formation and ignition under current engine relevant conditions - Vogel, Thomas; Wensing, Michael; Leipertz, Alfred; Iannuzzi, Stefano; Lutz, Michael (SAE Technical Papers, 2011)
Flexible and multiple injections are an important strategy to fulfill today's exhaust emission regulations. To optimize injection processes with an increasing number of adjustable parameters knowledge about the basic mechanisms of spray breakup, propagation, evaporation and ignition is mandatory. In the present investigation the focus is set on spray formation and ignition. In order to simulate current diesel-engine conditions measurements were carried out in a high-temperature (1000 K) and high-pressure (10 MPa) vessel with optical accesses. A piezo servo-hydraulic injector pressurized up to 200 MPa was used to compare four single injection durations and four multi-injection patterns in the ignition phase. All measurements were performed with CEC RF-03-06, a legislative reference fuel. For the spray measurements, a program of 16 to 18 different operating points was chosen to simulate engine conditions from cold start to full load. Two cameras were applied to take images from the UV and the visible part of the flame emission, indicating high temperature OH (premixed combustion) and soot luminosity (diffusion controlled combustion). The results showed that the key parameters influencing the ignition delay are the temperature of the ambient air and the injection pressure controlling the droplet size distributions, while air-pressure influences the location of the ignition. The amount of injected fuel does not noticeably change the ignition delay but does impact the location of ignition and the intensity. At all operating points investigated the ignition started on the front or the side of the tip of the fuel gas-phase. UV-signals could be recorded at all operating conditions before start of the visible flame. For each operating point the probability of ignition (temporally and spatially resolved) was calculated from the measurements to indicate the stability of the ignition process for the different operating conditions and fuel masses. For the multiple injections, it turned out that a burning or just-extinguished flame of a pre-injection clearly affects the ignition behavior of the main injection. The pre-injection and the corresponding flame are located very close to the nozzle tip which ignites the main spray earlier and closer to the nozzle. The overall area covered by the flame is clearly bigger for both, the UV- and the visible flame spectra in the case of multiple injections. © Copyright 2011 Society of Automotive Engineers of Japan, Inc. and SAE International.
Created from Fastlane, Scopus look-up